Performance Analysis of AF Relaying Cooperative Systems with Relay Selection Over Double Rayleigh Fading Channels - Ilhan, Haci; Akin, Ayse Ipek (IEEE, 2012)
In this paper, a performance analysis of amplify-and-forward (AF) relaying cooperative diversity system with relay selection is analyzed when source and destination are moving while relays are access point. We have derived analytical expressions for probability density function (PDF), cumulative distribution function (CDF) and moment generating function (MGF) of end-to-end signal-to-noise ratio (SNR) for the considered system. By using the CDF expression, the outage probability (Pout) of considered system is obtained. Then, the symbol error rate performance (SER) of the system is calculated for MPSK modulation assuming the source-to-destination link has double Rayleigh distribution while the source-to-relays and the relays-to-destination links have Rayleigh distribution.
Keywords: Cooperative communication; Amplify-and-forward; Relay selection; Double Rayleigh fading; DIVERSITY; MODEL; Engineering; Telecommunications